Divergent Paths of Neo-Endogenous Rural Development: A Comparative Analysis of Rural Villages in South Korea (London Journal of Research In Science: Natural and Formal, 2024)
The paper is to compare two villages in Songak-myeon, Asan, Cnungnam Province in Korea. It tries to show how the joint village project, which began with the support of the same external organization, produces different results depending on the internal conditions and circumstances of the village. From the end of the 1990s, Pyeongchon-ri and Sugok-ri started developing villages under the influence of the environmentally friendly farming movement. And subsequent supports were provided by local organizations for the development of the village. However, the village project in Sugok-ri, which focused on economic performance, later turned out to be a failure, and the residents changed to pursue activities for their own economic interests individually. On the other hand, In Pyeongchon-ri, the cooperation among villagers was strengthened in implementing support projects by similar external agencies. In addition, community ties and identity have been strengthened as problems have been solved through cooperation among residents in the process of promoting the village project. Nevertheless, projects undertaken in Pyeongchon-ri for the purpose of increasing economic performance was all failed. Through these findings, the paper asserts that the neo- endogenous development approach utilizing external support based on internal cooperative network among villagers must be a very useful method for rural development in contemporary societies.
Keywords: Energy Optimization; Sustainable Energy Practices; ESG Metrics Integration; Chinese Industrial Energy; Environmental Efficiency; Econometric Energy Analysis; IM evaluation; genre-based instructional material; reading proficiency; participation; Neo-Endogenous development; Exogenous and Endogenous development. Network; Village development. Environmentally Friendly Agriculture. Hansalim.